2022
DOI: 10.3390/ijerph191610373
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Perceptron-Based Real-Time Intradialytic Hypotension Prediction Using Patient Baseline Information and Heart-Rate Variation

Abstract: Intradialytic hypotension (IDH) is a common side effect that occurs during hemodialysis and poses a great risk for dialysis patients. Many studies have been conducted so far to predict IDH, but most of these could not be applied in real-time because they used only underlying patient information or static patient disease information. In this study, we propose a multilayer perceptron (MP)-based IDH prediction model using heart rate (HR) information corresponding to time-series information and static data of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…MLP is a neural network composed of multiple layers of interconnected nodes, each performing a simple computation on the input data. MLP is commonly used for problems with complex, nonlinear relationships between input and output variables [30].…”
Section: Role Of Machine Learning In Blood Glucose Measurementmentioning
confidence: 99%
“…MLP is a neural network composed of multiple layers of interconnected nodes, each performing a simple computation on the input data. MLP is commonly used for problems with complex, nonlinear relationships between input and output variables [30].…”
Section: Role Of Machine Learning In Blood Glucose Measurementmentioning
confidence: 99%
“…Yeon Jo et al reported an AUC score of 0.957 (0.954–0.960) using ABP, ECG, and electroencephalogram (EEG) signals as input to deep learning models using ResNet architecture, which contains 12 residual blocks and one linear layer. [ 40 ] Moreover, Bae et al used heart rate information corresponding to time series data and patient baseline information as input to a multilayer perceptron [ 41 ]. Their study aim was to validate heart rate difference and heart rate slope features correlated with hypotension conditions.…”
Section: Introductionmentioning
confidence: 99%